Energetic and exergetic aspects of solar air heating (solar collector) systems - Öztop, Hakan Fehmi; Bayrak, Fatih; Hepbasli, Arif (Pergamon-Elsevier Science Ltd, 2013)
Solar air heating (solar collector) is a renewable heating technology and provides heat using solar energy. With fuel costs and other factors, solar air heaters (SAL-Is) are getting more attention. The energetic and exergetic performance of SAHs is influenced by a number of factors. The present study reviews the previously conducted studies and applications in terms of design, performance assessment, heat transfer enhancement techniques, experimental and numerical works, thermal heat storage, effectiveness compassion and recent advances. It may be concluded that energy analysis method has been used in a number of studies while exergy analysis method has been applied to the relatively low numbers of systems. Energy efficiencies of solar air collectors reviewed varied from 47% and 89%. It is expected that this comprehensive study will be very beneficial to everyone involved or interested in the energetic and exergetic design, simulation, analysis, test and performance assessment of SAHs. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Solar energy; Solar air heater; Exergy; Heat transfer enhancement; Renewable energy